PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 SAWAHLUNTO TAHUN PELAJARAN 2013/2014 - Harmailia, Iis; Aima, Zulfitri; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research is by an understanding of mathematical concepts students are still low and low-ability students who are just waiting for an answer from the teacher. The study aims to determine whether the student understanding of mathematical concepts with the application of cooperative learning strategies Team Assisted Individualization (TAI) better understanding of the mathematical concepts that students applying conventional teaching class VIII SMPN5 Sawahlunto academic year 2013/2014. This research is experimental, with random design on the subject. The instrument used was an essay test and observation sheets. Hypothesis testing using the U Mann-Whitney test with the MINITAB program obtained p-value = 0.0077 is less than Î±, then reject H0. So it can be concluded that the students understanding of mathematical concepts by implementing cooperative learning strategies Individuaization Team Assisted Individualization better understanding of the mathematical concepts that students applying conventional learning.